‘FEMINIST’ BUDDHISM AND WOMEN EMPOWERMENT FROM A CONTEMPORARY CHINESE PERSPECTIVE - Wang, Xing (Journal of Dharma, 2022)
As the United Nations’ 2030 Agenda for Sustainable Development Goals has proposed, eliminating all possible gender inequalities is of priority for a more sustainable and progressive human society. Buddhist religion cannot avert such a modern agenda. But how such a goal can be achieved varies hugely, especially in the Chinese context. Rather than seeing the rise of ‘Feminist’ critique of Buddhism in both mainland China and Taiwan as homogeneous to Western feminist movements in religion, this article tries to reveal the diverse approaches of Chinese Buddhist elites to reconcile gender equality issues with Chinese Buddhist doctrines and other traditions in China. In particular, this article shows that certain Buddhists in mainland China deny the possibility of launching a Western-like ‘Feminist’ purge of Buddhism and argue that for sustainable development of both Buddhism and Chinese society, Buddhist traditions should not be put in the opposite to gender equality. It means that not only a separation between normative Chinese Buddhism and Buddhism as a social reality is needed, but that within the sphere of normative Buddhism, the ‘worldly dharma’ and the ‘transcendental dharma’ should be treated with more nuanced perspectives.